CRIMINAL THINKING NARAPIDANA KASUS PENCURIAN DI RUMAH TAHANAN NEGARA KELAS II B DEMAK - Ariyanto, Agus (Politeknik Ilmu Pemasyarakatan, 2025)
Humans as social beings need interaction with other people in meeting their needs. The increasingly complex needs with the development of the times allow someone to do practical things in fulfilling their needs by committing the crime of theft. Based on criminal statistical data in 2020, theft crime became the most cases that occurred during 2019. Theft is one of the crimes against property or wealth regulated in Chapter XXII Articles 362-365 of the Criminal Code which consists of four types of theft crimes including ordinary theft, theft weighting, light theft, and violent theft. one of the factors in the study of criminology and legal psychology states that cognitive factors can make a person commit a crime. Criminal thinking can be used as one of the terms in understanding a criminal in legitimizing the crime committed. According to Knight (2006), criminal thinking includes six aspects consisting of demanding rights, justification, level of aggressiveness, cold- bloodedness, rationalization of crime, and feelings of irresponsibility. This research what aspects play a role in criminal thinking in convicts of theft cases. The purpose of this research is to identify and identify aspects that play a role in the criminal thinking of convicts in the theft case at the Class II B Demak State Detention Center so that it can be used as a guide in providing the right coaching program.. The method used in this research is descriptive quantitative using the Criminal Thinking Scale (CTS) which was developed by Knight in 2006 as many as 36 items to 42 male inmates in the case of theft of articles 362-365 of the Criminal Code in the Class II B State Detention Center Demak. The results obtained in this study indicate that the highest aspect of criminal thinking in the theft case is found in the rationalization aspect of crime with a mean value of 15.50. The coaching program that can be given to inmates in cases of theft in every aspect of criminal thinking includes demanding rights with self-reliance development programs, justification with CBT therapy, aggressiveness level with religious coaching programs, cold-bloodedness with increased empathy, rationalization of crimes with legal counseling, and feelings of inadequacy. responsible for the attitude and mental development program.